1990
DOI: 10.1177/0115426590005003118
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience With Three‐in‐One Admixtures Administered Peripherally

Abstract: The purpose of this report was to describe the tolerance of hyperosmolar nutritionally complete solutions infused peripherally, as a bridge to enteral therapy in the surgical patient. Solutions providing approximately 40% of calories as carbohydrates were administered to 23 surgical patients with the fats, amino acids, and dextrose mixed in one container. Final osmolarity, when measured directly with additives, ranged from 1200-1350 mOsm/L. Approximately 85% of the patients had acceptable tolerance to this new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Dextrose and amino acids are significant contributors of solution osmolarity. Other factors that may influence the incidence of thrombophlebitis include addition of heparin, 31,32 addition of corticosteroid, 31 or the presence of fat emulsion when PPN is prepared as a TNA. [32][33][34][35] The coinfusion of intravenous fat emulsion (IVFE) has not been shown to reduce phlebitis.…”
Section: Strongmentioning
confidence: 99%
See 1 more Smart Citation
“…Dextrose and amino acids are significant contributors of solution osmolarity. Other factors that may influence the incidence of thrombophlebitis include addition of heparin, 31,32 addition of corticosteroid, 31 or the presence of fat emulsion when PPN is prepared as a TNA. [32][33][34][35] The coinfusion of intravenous fat emulsion (IVFE) has not been shown to reduce phlebitis.…”
Section: Strongmentioning
confidence: 99%
“…Other factors that may influence the incidence of thrombophlebitis include addition of heparin, 31,32 addition of corticosteroid, 31 or the presence of fat emulsion when PPN is prepared as a TNA. [32][33][34][35] The coinfusion of intravenous fat emulsion (IVFE) has not been shown to reduce phlebitis. 36,37 All available studies that have evaluated peripheral vein thrombophlebitis with infusion of PPN are limited by small sample size.…”
Section: Strongmentioning
confidence: 99%
“…4,5 There are several studies describing adverse events in peripherally administered hyperosmolar parental nutrition; however, there are limited data regarding the safety of sodium chloride 3% via this route in an acute setting. [6][7][8][9][10][11][12][13][14] When specifically evaluating sodium chloride 3%, there is currently no published literature in the adult population. Retrospective studies in the pediatrics population have found that patients who received these infusions peripherally had no evidence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A PN formulation contains a mixture of hypertonic dextrose, amino acids, electrolytes, and vitamins, thereby resulting in hyperosmolar solutions. 4,5 The intravenous access site used for a given PN formulation is dictated by the osmolarity. High-osmolarity PN formulations infused into a peripheral vein will damage the vessel and require frequent changes of injection site.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The risk of vascular damage increases when PN formulation osmolarity rises above 600 mOsm/L, and the peripheral vein cannot tolerate an osmolarity >900 mOsm/L. [5][6][7][8][9] Isaacs et al 6 reported that PN with an osmolarity of 900 mOsm/L infused infused via peripheral veins was rapidly stopped about 4 ± 3 hours at a particular site because of local phlebitis reactions consisting of pain, erythema, swelling, or heating. Timmer et al 7 demonstrated that a PN osmolarity of 1,044 mOsm/L may induce a 91% phlebitis rate after 2.8 days of peripheral venous feeding.…”
Section: Introductionmentioning
confidence: 99%